The Perception of Child-Rearing Goals among Surinamese Teachers and Parents - Marshall, Edvin; Van der Wolf, Kees (International Journal about Parents in Education, 2023)
This explorative study is a first step towards more extensive research into the child-rearing goals and parenting styles used in Suriname’s multiethnic society. We tried to find out whether there are in fact differences in parenting and child-rearing ideals between Surinamese parents and teachers and among Surinamese parents and teachers of different ethnic origins. We have obtained our data by presenting 36 statements about child-rearing goals to 155 teachers and 142 parents and asking them to order them according to the q-sort method. This study has established that there are almost no significant differences between parents and teachers and among the various ethnicities within these two groups. This is contrary to the older literature on child-rearing goals and parenting styles in Suriname, which found greater differences among groups on the basis of anthropological methods like interviews and observations. The absence of differences could indicate that the ethnic groups are converging as far as values and standards are concerned. This finding should, however, be approached with due care since our sample is still small and has been limited to the urban and more highly educated part of the population.